Seroprevalence for Rickettsia spp. and Borrelia spp. in horses from non-endemic areas at the Southeastern Brazil - Gonçalves, Elaine Santana; Cordeiro, Matheus Dias; Fonseca, Adivaldo Henrique da; Figueiroa, Thays; Araújo, Izabela Mesquita; Labruna, Marcelo Bahia; Guedes, Elizângela (International Journal of Advanced Engineering Research and Science, 2021)
Spotted Fever Group (SFGR) and Baggio-Yoshinari Syndrome (BYS) are described as important tick-borne zoonosis. Horses do not participate directly in the cycle of these diseases, but they work as sentinels of epidemiological studies. We analyzed the distribution of Rickettsia spp. and Borrelia spp. in horses and ticks of two non-endemic areas from Southeastern Brazil. Blood serum from 102 horses of different ages (> 12 months) and breeds were analyzed by the indirect immunofluorescence reaction (IFR) with the aid of specific antigens for R. rickettsii, R. parkeri, R. rhipicephali, R. amblyommatis and R. bellii, besides the indirect immunoadsorption assay (ELISA) aiming to detect homologous IgG antibodies against B. burgdorferi (American strain G39/40). Free-living and parasitic ticks were collected for PCR and Nested-PCR tests to detect both Rickettsia spp. (citrate synthase gene) and Borrelia spp. (flagellin gene). The data showed 51.96% (53/102) of seropositive horses at least in one of the five tested Rickettsia antigens, and 10.78% (11/102) were considered serum-specific for R. parkeri. Besides that, a total seroprevalence of 13.73% (14/102) for immunoreactive antibodies of the IgG class against B. burgdorferi were obtained from the indirect ELISA. Three hundred and fifty-three ticks were collected, all identified as Amblyomma sculptum and negative for PCR and Nested-PCR. The obtained results suggest the circulation of SFGR and Borrelia spp. in a non-endemic area of Brazil, added to a large occurrence of vector ticks. This scenario deserves attention for the possibility of a zoonotic cycle in the region.